Digital Pedagogy: Experience of Advanced Training - E. V. Bryzgalina; D. A. Alekseeva; E. D. Dryaeva (Высшее образование в России)
The purpose of this study is to analyze the results of the professional development program “Digital Pedagogy of the Modern University” held at the Philosophy Department of Moscow State University. In today’s increasingly mediated everyday life by digital technologies, the Internet, and virtual communicative environments, traditional education is getting a new  lease of life. While digital devices have long been an integral part of modern  life, social, cultural and educational institutions are struggling to keep up with the rapid pace of change. As the coronavirus spread across the world, universities moved classes online to prevent coronavirus spread. The program “Digital Pedagogy of the Modern University” was aimed not at the permanent movement from face-to-face to online education but the desire to implement an interim solution for emergency remote teaching and  discuss the challenges. During the program, the organizers considered both  methodological issues of creating courses and current trends in educational development, psychological aspects of network communications in a distance learning, and much more. The emphasis was made on the reflection  of moving to online teaching. The survey on the results of the program showed that the impact of the experience of distance learning was a complex phenomenon. This study may serve as a basis for further  discussion.